Designing Potent Anticancer Peptides by Aurein 1.2 Key Residues Mutation and Catenate Cell-Penetrating Peptide - Hamta Salarpour Garnaie; Arman Shahabi; Mohammad Hossein Geranmayeh; Abolfazel Barzegar; Ahmad Yari Khosroushahi (Tabriz University of Medical Sciences, 2023)
Purpose: Aurein 1.2 (Aur) peptide is known for possessing anticancer characteristics devoid of conventional therapeutics side effects. For improving Aur peptide anticancer functionality, different anticancer peptides were constructed based on Aur peptide through targeting two separate strategies, including (1) sequence-based mutations and (2) adding a cell-penetrating peptide linker. Methods: The study was approached by designing three different analogs of Aur, including (a) Aur mutant (Aurm), (b) Aur with N-terminal polyarginine linker (R5-Aur), and (c) Aurm with R5 (R5-Aurm). Computational molecular dynamics simulations clearly showed higher structural stability of R5-Aur and R5-Aurm compared to Aur, solely. The α-helical properties of R5-Aur and R5-Aurm were protected during 500 ns simulations in water solution while no such structural conservation was seen for Aur in silico. Results: The results of the current study highlight response to one of the main challenges of cancer therapy through selective invasion of Aur to cancer cells without significant involvement of normal cells. This issue was confirmed by different assays, including: MTT assay, flow cytometry, qPCR, and nuclei morphological observations. Furthermore, this study intensifies exploiting in silico approaches for adjusting drug delivery. The results of different assessments on designed peptides reveal an anticancer activity pattern rising from Aur toward Aurm, and R5- Aur, consecutively. Conclusion: The designed structure of Aur shows improved anticancer activity through molecular changes which makes it suggestable for anticancer therapies.